The Urgency of Islamic Religious Education in Instilling the Practice of Salat Among at Elementary Students: Education and Da’wah Perspective - Syafaruddin, Baso; Muhsyanur, Muhsyanur; Jumhuriani, Jumhuriani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This article investigates the process of Islamic Religious Education (PAI) at UPTD SD Negeri 181 Bulete, Pitumpanua Subdistrict, Wajo Regency, with a focus on the students' practice of Salat and the efforts of teachers in guiding its implementation. Using a qualitative approach with pedagogical, religious, and psychological perspectives, the study analyzes primary and secondary data through interviews, observations, documentation, and questionnaires. The findings reveal that the implementation of PAI involves three key components: preparation, which includes curriculum and lesson planning; the learning process, which focuses on the teacher’s ability to explain, the use of methods, and learning media; and evaluation, including feedback, tasks, and grades. The study also shows that the practice of Salat among students is still in the learning stage, with some students accustomed to it due to guidance from teachers and parents. Teachers play a vital role in this process by providing advice, being role models, and offering motivation. This study underscores the importance of Islamic Religious Education in shaping students' religious practices, particularly in the context of Salat, and highlights the significant role of teachers in this guidance.